Identifying Conservative Interventions for Individuals with Subacromial Pain Syndrome Prior to Undergoing a Subacromial Decompression: A Scoping Review - Joseph A Signorino; Aubrey G. Thompson; Benjamin R Hando; Jodi L Young (North American Sports Medicine Institute, 2023)
# Background Subacromial decompression (SAD) surgery remains a common treatment for individuals suffering from subacromial pain syndrome (SAPS), despite numerous studies indicating that SAD provides no benefit over conservative care. Surgical protocols typically recommend surgery only after exhausting conservative measures; however, there is no consensus in the published literature detailing what constitutes conservative care "best practice" before undergoing surgery. # Purpose To describe conservative interventions received by individuals with SAPS prior to undergoing a SAD. # Study Design Scoping review. # Methods An electronic search using MEDLINE, CINAHL, PubMed, and Scopus databases was conducted. Peer-reviewed randomized controlled control trials and cohort studies published between January 2000 and February 2022 that included subjects diagnosed with SAPS who progressed to receive a SAD were eligible. Subjects who received previous or concurrent rotator cuff repair with SAPS were excluded. Conservative interventions and treatment details that subjects received prior to undergoing a SAD were extracted. # Results Forty-seven studies were included after screening 1,426 studies. Thirty-six studies (76.6%) provided physical therapy (PT) services, and six studies (12.8%) included only a home exercise program. Twelve studies (25.5%) specifically detailed the delivered PT services, and 20 studies (42.6%) stated who provided the PT interventions. Subacromial injections (SI) (55.3%, n=26) and non-steroidal anti-inflammatories (NSAIDs) (31.9%, n=15) were the next most frequently delivered interventions. Thirteen studies (27.7%) included combined PT and SI. The duration of conservative care varied from 1.5 months to 16 months. # Conclusion Conservative care that individuals with SAPS receive to prevent advancement to SAD appears inadequate based on the literature. Interventions, such as PT, SI, and NSAIDs, are either underreported or not offered to individuals with SAP prior to advancing to surgery. Many questions regarding optimal conservative management for SAPS persists. # Level of Evidence n/a